2008
DOI: 10.1007/s10856-008-3561-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the hard segment chemistry and structure on the thermal and mechanical properties of novel biomedical segmented poly(esterurethanes)

Abstract: Two series of biomedical segmented polyurethanes (SPU) based on poly(epsilon-caprolactone) diol (PCL diol), 1,6-hexamethylene diisocyanate (HDI) or L: -lysine methyl ester diisocyanate (LDI) and three novel chain extenders, were synthesized and characterized. Chain extenders containing urea groups or an aromatic amino-acid derivative were incorporated in the SPU formulation to strengthen the hard segment interactions through either bidentate hydrogen bonding or pi-stacking interactions, respectively. By varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 28 publications
5
82
0
3
Order By: Relevance
“…A bioresorbable SPEU named PHD was synthesized from aliphatic diisocyanate, aliphatic polyester, and a diester-diphenol chain extender according to previously reported procedures (Caracciolo et al, 2009). Dichloromethane (DCM) and N,N-dimethylformamide (DMF) were acquired from Anedra (BA, Argentina).…”
Section: Methodsmentioning
confidence: 99%
“…A bioresorbable SPEU named PHD was synthesized from aliphatic diisocyanate, aliphatic polyester, and a diester-diphenol chain extender according to previously reported procedures (Caracciolo et al, 2009). Dichloromethane (DCM) and N,N-dimethylformamide (DMF) were acquired from Anedra (BA, Argentina).…”
Section: Methodsmentioning
confidence: 99%
“…Caracciolo et al [20] reported the preparation of two series of biomedical segmented polyurethanes (SPU) based on PCL, HDI or LDI and three different chain extenders. Chain extenders containing urea groups or an aromatic amino-acid derivative were incorporated in the SPU formulation to strengthen the hard segment interactions through either bidentate hydrogen bonding or π-stacking interactions, respectively.…”
Section: Hard Segmentsmentioning
confidence: 99%
“…Here it should be noted that several reactants commonly used in PU formulations such as, for example, 4,4'-diisocyanatodiphenylmethane (MDI) or 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA or MBOCA), degrade to toxic products and therefore have to be excluded from the synthesis of BioPUs. The choice of reactants in order to obtain polymers with non-toxic degradation products, which will give a medical implant with good mechanical properties, is the main challenge of the production of novel BioPUs [18][19][20]. The development of properly biodegradable PU materials with appropriate mechanical and target functional properties (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Otros investigadores también reportaron la síntesis de PUs biorreabsorbibles usando extensores de cadena novedosos [121][122][123]. A pesar de su rol central, la síntesis de PUs asistida por esta tecnología ha sido estudiada de forma muy limitada y la mayoría de los estudios se centraron principalmente en los aspectos químicos de la vía de síntesis y las características moleculares obtenidas.…”
Section: Poliuretanosunclassified